Expression of aFGF and FGF9 in the developing rat retina - Çayırlıoğlu, Pelin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Sciences and Engineering, 1995., 1997)
aFGF, an FGF gene family member, has been postulated to be important in the physiology and development of vertebrate retina. The distribution and relative levels of aFGF mRNA in the external photoreceptors layer, and in the internal layer, containing the interneurons, Muller and the ganglion cells, were analyzed by RT-PCR and Southern hybridization techniques during development. This approach provides high specificity defined by specific primers, characterization of the PCR product by restriction digestion and/or hybridization with nested oligonucleotide probes. To compare the transcript levels, amplifications were performed at exponential phases. aFGF was detected in both layers, which unequivocally places aFGF expression to the inner layer cells. Its expression pattern suggests that aFGF may be involved in developmental events subsequent to the photoreceptor differentiation and in the further maturation of the retina. The difference in the aFGF expression patterns in two layers suggest aFGF may play different roles in different layers. The widespread expression of FGF9 in the central nervous system raises the possibility of its presence in the retina. Using RT-PCR we show that FGF9 is present in all postnatal days and embryonic day 17. Thus, it might be mitogenic, and survival factor for the retinal cells.
Keywords: Fibroblast growth factors.; Retina -- Growth.